CHRONIC PERICORONITIS MANAGEMENT WITH OPERCULECTOMY USING SCALPEL: TATALAKSANA PERIKORONITIS KRONIS DENGAN OPERKULEKTOMI MENGGUNAKAN SCALPEL - Eka Pramudita Ramadhany; Media Sukmalia Adibah; Putu Fenti Surya; Dwis Syahrul (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Pericoronitis is defined as inflammation of the gingiva caused by infection of the soft tissue around a partially erupted tooth. Pericoronitis is caused by the accumulation of food debris under the operculum surrounding a partially erupted tooth, which provides a place for a wide variety of polymicrobial flora. The most common area for pericoronitis is the partially erupted lower third molar. According to the international classification, pericoronitis can be classified as acute and chronic. Case: A 23-year-old female patient came with complaints of pain in the lower left side. Clinical and radiographic examination showed 38 partially erupted teeth with vertical grade 1 A impaction. The operator decided to perform operculectomy on tooth 38. Case Treatment: The procedure was carried out under infiltration anesthesia with lidocaine HCl + epinephrine, the incision was made using a blade no.12 on the bleeding point that had been made previously, after excision of the operculum, the operating area was irrigated with saline solution and controlled bleeding with the application of a periodontal pack. Discussions: After one week of control, there was still redness and pain when palpated, then oxyfresh gel was applied. four week follow up shows, there was no redness, and pain when palpated. Wound healing after operculectomy looks good, no reccurent and inflammation sign and the patient has no complaints Conclusion and Suggestions: Operculectomy can be the main therapy in cases of pericoronitis with vertical IA and partial eruption.